Tax Potential in The Pandemic: Myths and Reality - Lidiya MAZUR; Irina TRUBINA; Olga RUDAKOVA; Nataliya LYSENKO (Communications of International Proceedings, 2020)
Tax potential for any state is the source of its revenues as well as expenditures. In the global pandemic there is a trend in reduction of state revenues with a significant increase in expenditure obligations, both in the social sphere and in the real sector of the economy in order to support business. The issues related to solving medical problems, which also require substantial funding come to the foreground. This determines the urgency of the problem of stimulating the tax potential. The purpose of the study is to assess the sources of formation of tax potential in the pandemic. Based on the analysis of official statistical information, trends in the dynamics of tax potential were identified, and a comparative assessment of monthly tax revenues over several years was carried out. The trend of reduction of the real volume of tax revenues for each tax is revealed.
Keywords: Budget System; Tax Potential; Revenues; Taxes; Economic Instability; Pandemic